PERUBAHAN STATUS WALI ADHAL MENJADI WALI JAUH UNTUK MENDAPATKAN HAK WALI HAKIM DALAM PERNIKAHAN - kusnan, kusnan; Harahap, Pangeran (AT-TAFAHUM: Journal of Islamic Law, 2017)
In the regulation of wali adhal, stated that by the condition of wali adhal or reluctance, the wali hakim then just can subtitute to be a wali nikah after the decision made by religious court, in office of religious affairs it was found 10 couples went far away from their true wali, in order that the guardian right goes to wali hakim. This legal research is conducted to figure out social phenomenon about legal implementation in society, it is qualitative research based on interview and document study, which of has purpose on finding the backround of the problem causing them to change the wali adhal to be wali jauh.The result shows that the cause which makes the couple change the status of wali adhal to be wali jauh are: (1) The understanding of couple about aloping; (2) Community culture about eloping followed by couples; (3) The couple do not understand the procedure of wali adhal; (4) The couple have too short time and no enaugh money to get married.